Pengembangan Modul Pembelajaran pada Kegiatan Ekstrakurikuler Pramuka Penggalang untuk Meningkatkan Keterampilan dan Karakter Siswa di SD Negeri 104267 Pegajahan - Andira, Nurul; Sukmawarti (Melati Institute, 2024)
Scouting is an extracurricular activity that has become part of the education system in Indonesia. Learning modules in the extracurricular activities of the Cub Scouts are developed based on the Scout curriculum that has been established by the Indonesian Scout Movement. However, in reality, at SD Negeri 104267 Pegajahan it is still found that teachers who make scout learning modules are not in accordance with the needs in designing effective and quality modules which can cause learning modules that are less interactive, less interesting, or less targeted. In this study, researchers used a development research design or better known as Research and Development (R&D). The Research & Development method is a research method used to produce a particular product, and test the effectiveness of the product. This research was designed with the ADDIE development model. The ADDIE model consists of five development steps, namely: (1) analyze, (2) design, (3) develop, (4) implement, and (5) evaluate (Tegeh, 2014: 42) The results of this study refer to research and development which has five stages. However, researchers only use three stages, namely the analysis stage, the design stage, and the development stage. The module teaching materials developed are valid and ready to use with a score of 77.65% from module experts and 77.33% from material experts with each criterion “Valid, can be used but needs minor revisions” so that the module can be used or applied in extracurricular activities later.